1974
DOI: 10.1136/gut.15.7.521
|View full text |Cite
|
Sign up to set email alerts
|

Faecal fat excretion after truncal, selective, and highly selective vagotomy for duodenal ulcer

Abstract: SUmmARY Faecal fat excretion was measured on a metabolic ward in 16 patients with duodenal ulcer before operation, and in patients who were in good health more than one year after truncal vagotomy and pyloroplasty (n = 11), bilateral selective vagotomy and pyloroplasty (n = 9), or highly selective vagotomy without a drainage procedure (HSV, n = 12). Excretion of faecal fat was significantly greater (P < 0.01) in patients after both truncal and selective vagotomy with drainage than in patients before operation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…From studies of groups of patients we know that increased faecal fat excretion may occur in various gastrointestinal diseases (12)(13)(14) and that faecal fat excretion reflects the severity of the disease (14). An exact estimation of lipid assimilation may be difficult.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From studies of groups of patients we know that increased faecal fat excretion may occur in various gastrointestinal diseases (12)(13)(14) and that faecal fat excretion reflects the severity of the disease (14). An exact estimation of lipid assimilation may be difficult.…”
Section: Resultsmentioning
confidence: 99%
“…This group consisted of patients with a) diseases compatible with malassimilation (12)(13)(14) but in whom faecal fat was within normal limits (no. Patients with probable abnormalities in lipid assimilation (no.…”
Section: Subjectsmentioning
confidence: 99%
“…First, we must consider the absorptive function because the absorption of nutrients from the intestine is necessary for GIP re lease [18]. Some investigators have suggested that TV with pyloroplasty reduces fat absorp tion [19,20]. There is a possibility, therefore, that the apparent GIP response to fat did not change after TV, even though TV might di rectly increase the reactivity of the GIP cells to fat as well as to glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients lose weight after gastric surgery; as a consequence malnutrition and specific nutritional deficiencies may develop. Mild steatorrhea is common after gastric surgery (table 1), but daily fecal fat output seldom exceeds 15% of fat intake [17,18]. Different factors may contribute to this effect: (1) impaired pancreatic and biliary secretory responses; (2) normal pancreaticobiliary secretions, but a changed, unfavorable ratio between food and digestive juices; (3) accelerated transit of chyme through the small intestine leading to insufficient time available for digestion; as a consequence undigested food reaches the colon; (4) after distal gastrectomy, pieces of food larger than 1 mm empty from the stomach into the Degen/Beglinger small intestine.…”
Section: Effect Of Gastric Surgery On Digestive Functionsmentioning
confidence: 99%